Infectious endocarditis x dental treatment: Literature review (Research, Society and Development, 2023)
Introduction: Infective endocarditis is a rare but serious condition that affects heart valves. Dental procedures can pose a risk for this condition, highlighting the importance of preventive dentistry and knowledge of prophylactic guidelines by dentists. The use of antibiotics is essential in preventing endocarditis and must follow international guidelines. Objectives: Identify and establish risk groups for endocarditis related to dental procedures, highlight the role of the dentist in prevention, and address the conduct discussed in predisposed patients, with an emphasis on guidelines for the use of precautions. Methodology: 9 articles were selected after bibliographic research in the Scielo, PubMed and ScienceDirect databases, with inclusion criteria of articles published between 2018 and 2023 in Portuguese and English. Results: There are several guidelines for antibiotic prophylaxis, with variations over time. The American Heart Association (AHA) has recommended prophylaxis since 1955, but there have been changes. NICE discontinued one recommendation, while Brazilian and inter-American guidelines still recommend it for high-risk patients. Conclusion: It was found that patients with a history of previous infective endocarditis, cardiac valve prostheses, uncorrected cyanotic congenital heart disease, among other specific conditions, are considered at high risk for developing IE after invasive dental procedures.